Digital literacy matters. Increasing workforce productivity through blended English language programmes. - Kshema Jose (Higher Learning Research Communications, 2016)
The three Rs, the ability to read, write and do basic arithmetic have traditionally been measured as indicators of knowledge and ability to communicate, and in turn, a predictor of success at workplace. However, survey any place of work today, and we see that the traditionally held literacy skills do not suffice; newer forms of literacies that go beyond the ability to decode print, like the skill to communicate, interact, solve complex problems, analyse, judge, evaluate, collaborate, construct, create, and to use information technology/ digital tools, are now considered essential contributors to enhanced employability opportunities as well as workplace success.